Properties of a-C:H films deposited in CH4 H2 and CH4he DC plasma - Awang, R.; Rahman, S.A. (2009)
Hydrogenated amorphous carbon (a-C:H) films were deposited using direct-current plasma enhanced chemical vapor deposition (DC PECVD) process. The resulting film properties were studied with respect to the introduction of hydrogen (H2) and helium (He) in methane (CH4) plasma. The analysis techniques used to assess the film properties included optical transmission spectroscopy, Fourier transmission infrared (FTIR) spectroscopy and photoluminescence (PL) spectroscopy. Hydrogen dilution has significant effect on the deposition rate and optical band gap (Eg) of the film but helium dilution produces insignificant effects on these parameters. However, the hydrogen content in the film decreases steeply to a saturation value with increase in helium dilution. Increase in dilution of CH4 by both H and He gases result in decrease in PL efficiency. Â© 2009 World Scientific Publishing Company.